2017
DOI: 10.5070/d32311037249
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis lichenoides-like drug reaction: A clinical histopathologic study of 10 cases

Abstract: Figure 3. A) Phenotypic studies highlighting the infiltrate by the CD3 pan T-cell marker (200%). There is a predominance of B) CD8, (200%), to C) CD4, (200%). D) There is a marked reduction in the expression of CD7 (200%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…A clinical histopathologic study that reviewed 10 cases of pityriasis lichenoides-like drug reaction reported a paucity of inflammatory cells, with eosinophils noted in 1 case. 4 The histopathologic findings in our case align with the histologic characteristics of drug- and chemo-induced PLC, showing infiltration of lymphocytes in the papillary dermis and interface dermatitis with apoptotic parakeratosis, and a lack of eosinophils.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A clinical histopathologic study that reviewed 10 cases of pityriasis lichenoides-like drug reaction reported a paucity of inflammatory cells, with eosinophils noted in 1 case. 4 The histopathologic findings in our case align with the histologic characteristics of drug- and chemo-induced PLC, showing infiltration of lymphocytes in the papillary dermis and interface dermatitis with apoptotic parakeratosis, and a lack of eosinophils.…”
Section: Discussionsupporting
confidence: 81%
“… 5 One case report presents the case of an 83-year-old woman who developed PLC after receiving an anti-CCR4 monoclonal antibody. 4 Similar to our patient, she experienced symptoms months after initiating tafasitamab/lenalidomide therapy and her symptoms were exacerbated with each infusion.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…On histopathology, PLEVA demonstrates a T-cell dominant infiltrate, 4 and a dominant T-cell clone has been found in a majority of cases. 3 Magro et al 5 argued that PLEVA and PLC represent a form of T-cell dyscrasia based on the reduced expression of CD7 and CD62L, along with the presence of clonality. They also cited cases which evolved into mycosis fungoides as evidence of an underlying T-cell process.…”
Section: Discussionmentioning
confidence: 99%
“…17 The etiology of PL remains unclear, though several hypotheses exist in the literature, including an inflammatory response to infection, an immune-complex mediated hypersensitivity vasculitis, and an indolent T-cell lymphoproliferative disorder that can show T-cell monoclonality. [18][19][20][21][22][23][24][25][26][27] In any case, IL-36 does not appear to be a significant driver of inflammation in most cases of this disease.…”
Section: F I G U R E 2 (A) Representative Hematoxylin and Eosin (Hand...mentioning
confidence: 99%